1997
DOI: 10.1002/1521-396x(199710)163:2<403::aid-pssa403>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Study of Microstructure and Interfacial Interaction in Al–C60 Co-Evaporated Films

Abstract: Al–C60 thin films were prepared in vacuum by the co‐evaporation method. The structural and physical properties of the films have been studied with transmission electron microscopy and Raman scattering spectra. The growth of C60 crystallites is significantly limited by co‐deposition of aluminum. Raman spectra showed in these films that the Ag(2) pentagon‐pinch mode of C60 splits into two peaks, corresponding to the pristine and softened Ag(2) modes, respectively. The shifts of the softened Ag(2) mode are about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is also possible that in the latter regions negative charge transfer also occurs, but is counterbalanced by the oxidation-induced positive charge. A g (2) mode splitting due to charge transfer has also been reported in co-evaporated Al-C 60 films, 8 suggesting charge-transfer regions insulated from the rest of fullerite matrix.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is also possible that in the latter regions negative charge transfer also occurs, but is counterbalanced by the oxidation-induced positive charge. A g (2) mode splitting due to charge transfer has also been reported in co-evaporated Al-C 60 films, 8 suggesting charge-transfer regions insulated from the rest of fullerite matrix.…”
Section: Discussionmentioning
confidence: 82%
“…Q a , w a , data for additional features. in Al-C 60 co-evaporated films, 8 and also in Al-C 60 multilayers. 24 In our Cu-C 60 samples, H g 8 increases whereas H g 7 remains weak and broadens (Fig.…”
Section: Additional Raman Features and Disorder-related Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Among these, endohedral, Al‐coated, Al‐intercalated, and AlN fullerenes are inconsistent with the results, as explained by the following analysis: The endohedral fullerenes should cause hyperfine interactions with the central nitrogen atom ( I = 1) and aluminum ( I = 5/2), in the ESR measurements, but their ESR signals were not detected in the AlN precursor. In the cases of Al‐coated and Al‐intercalated fullerenes, their crystalline structures were reported to be fcc, which is different from that of the AlN precursor. AlN fullerenes are not observed experimentally, but their geometrical structures and electronic properties have been investigated theoretically .…”
Section: Discussionmentioning
confidence: 95%
“…To investigate the feasibility of C 60 layers, it is inevitable to obtain stronger and more stable C 60 films, keeping the original characteristics of C 60 films. It has been reported that the metal-C 60 interaction is stronger than the C 60 -C 60 van der Waals interaction [9][10][11]. Therefore, metal doping in C 60 films may produce much harder and chemically stable materials.…”
Section: Introductionmentioning
confidence: 99%